A Critical Assessment of the Contribution of Tourism Education in Creating Work force for the Tourism Industry: - (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Students graduating from a professional tourism program should have the knowledge andabilities that make them immediately useful to the industry. The goal of this research is to find out whatkinds of knowledge and abilities tourism professors and experts think their students will need tosucceed in the field. The research also contrasts the views of tourism professors and industry expertson the content and competencies taught in tourism degree programs throughout the nation. It isimportant to define what exactly constitutes educational tourism, a phrase that has been used todescribe trips that combine educational components with sightseeing and vacationing. Now, we arediscussing such topics as what drives students to study, how informal and formal learning interacts, andhow tourism might benefit local economies. Currently, this issue has been widely discussed in bothdeveloping and established countries, with an emphasis on lowering unemployment rates via trainingyoung people and making a contribution to education through the tourism industry. Given theimportance of the tourism industry to the economies of developing countries, it is essential to firstestablish a theoretical framework for studying the industry and developing methods to empower it. Wetake a close look at these issues and provide some solutions that might improve the quality ofinstruction given to vacationers. There is a wide range of issues that need to be addressed, including butnot limited to educational infrastructure, curriculum updates, educational quality, education,administration, skills, tourism education, placement, job possibilities, employment growth, andemployee happiness. Colleges that focus on the tourist industry continue to suffer from a decliningimage.